ETR 300 : Triple X Auto Clinic / Mohd. Nasir Othman ... [et al.] - Othman, Mohd. Nasir; Mohamed Hamdan, Mohamed Syaharim; Shahidan, Shahasrul Afzan; Zainal Abdin, Zulazri (2002)
XXX Auto Clinic is a business that provides three services at the same place that our customers will be rejuvenated and ever ready to face the challenges ahead. Administration is the most important element to ensure that a business will run smoothly or not. Marketing plan is a planning of a promotion or other activity to attract customers in order to give information about our business. Target market and market analysis is create to identify the market for our business. Another planning is financial plan and operational plan. Operational plan is important because it is just likes basic planning of our business because our business provide services to the customers. Operational plan will explain in detail to our customers about the operational activity that we done. The operatio11al are providing workshop, welding, and painting services at the same place that make our business are special. We are also providing breakdown services just in time wherever our customers are; since their location of breakdown still around Sungai Petani area. Another planning is financial plan. Financial plan is very important in running the business. Financial plan of XXX Auto Clinic is prepared in order to ensure the cash flow of money is allocated. Financial plan gives an overall view about business financial statement.